Efficient Implementation of High-Order Accurate Numerical Methods on Unstructured Grids - Li, Wanai (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
This thesis focuses on the development of high-order finite volume methods and discontinuous Galerkin methods, and presents possible solutions to a number of important and common problems encountered in high-order methods, such as the shock-capturing strategy and curved boundary treatment, then applies these methods to solve compressible flows.